Analisis Lama Fermentasi Kombucha Kulit Melon (Cucumis melo L.) Terhadap Aktivitas Antioksidan, pH, Kadar Alkohol, dan Vitamin C - Albertha Fausta Nabila; Ambarwati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the effect of fermentation duration on the chemical characteristics of melon peel kombucha (Cucumis melo L.), including vitamin C content, antioxidant activity, alcohol content, and pH value. The research method used was an experimental method with a Completely Randomized Design (CRD) consisting of one factor, namely fermentation duration of 8, 10, and 12 days. Data were analyzed using the Kruskal–Wallis test followed by Duncan’s multiple range test. The results showed that fermentation duration had a significant effect (p < 0.05) on vitamin C content, antioxidant activity, and alcohol content, but had no significant effect on pH value because the pH range remained relatively narrow and stable under acidic conditions during fermentation. The best treatment was obtained at 10 days of fermentation, with vitamin C content of 107.77 mg/100 g and antioxidant activity of 56.21%, while the lowest alcohol content was found at 12 days of fermentation at 0.5% with a pH value of 4.26. In conclusion, a fermentation period of 10 days was considered the optimum condition for producing melon peel kombucha.  Keywords: Antioxidant, Fermentation, Kombucha, Melon Peel, Vitamin C.